Decay of Entanglement of Correlated Qubits Through Bosonic Fields - Deniz Türkpençe (Indonesian Journal of Science and Technology, 2021)
Distribution of entangled parties with the longest time possible is of importance to quantum communication. Therefore, analyzing the decay character of entanglement of correlated qubits in the presence of reservoir effects is of significance to the quantum-based technologies. This study covers the analysis of the temporal entanglement decay of two maximally entangled qubits against different reservoir types and system parameters. It is shown how varying the coupling type of the system to the environment affects the lifetime of entanglement. In the presence of quantum interaction between entangled qubits, it is possible to enlarge the entanglement lifetime depending on the initialization of entanglement.  Model parameters used in the numerical calculations and the results are general enough to be applied in any specific quantum-based experimental task.